PENERAPAN TRANSMISI SISTEM PENGGERAK PADA ALAT PERAGA PEMOTONG KERTAS - Ansor Salim Siregar; Mohamad Sjahmanto; Regi Ramadhan; Muhammad Iqbal Yasin; Fikri Romadhon (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
Looking at the current situation, especially in Indonesia, every year there is turmoil due to the lack of job opportunities, this can be seen from the information circulating and data published both nationally and on social media. Community Service Program which will be carried out from the perspective of resource persons or those who will carry out the Tri Dharma of higher education to share insights into transmission drive systems. Nurul Ihsan Islamic Boarding School provides Islamic education as well as community empowerment in Momonggor Village Rt.001/01 Keranggan Village, Setu District, South Tangerang City, Banten. The gear transmission system is one of several existing power transmission systems (friction wheels, belts, chains, clutches). Gears are driving machine elements that transfer power by rotation from one shaft to another without slipping. The Islamic boarding school in question is one of the boarding schools that is located close to Pamulang University, so it can be said that it will have more impact if it is implemented at that boarding school because monitoring is easier regarding its development. The drive system transmission in the paper cutting tool can later be applied or recognized in various tools that use the drive system transmission. The drive system for the paper cutting prop that will be demonstrated is the work of Mechanical Engineering students at Pamulang University. When the PkM was implemented, the Santri and Community of the Nurul Ihsan Islamic Boarding School Foundation in South Tangerang looked very enthusiastic during the question and answer session. During the activities, the students and community of the Nurul Ihsan Islamic Boarding School Foundation in South Tangerang also seemed very motivated and active in the activities carried out by showing their great curiosity. Keywords : Transmission, Santri, Islamic Boarding School.